Evolución en las exportaciones de banano e impacto del desarrollo económico, provincia de El Oro 2011 - 2020, pre-pandemia, pandemia. - Acaro Chamba, Luz Maria; Cordova Montoya (My University, 2021)
The export of bananas is the first economic activity in the province of El Oro, which has generated a great impact in recent years on the economic development of the country, thus, it is one of the provinces with the highest percentage of exports nationwide. However, the official measures of mandatory confinement, due to the global pandemic of COVID-19, companies have been forced to take temporary measures such as reducing their production capacity for instance. Therefore, banana export activity is being seriously affected in this province. The present study aims on the analysis of the evolution of banana exports activity, and its impact in the economic development of the province of El Oro 2011-2020, pre-pandemic and pandemic period, by applying time series. This research is descriptive, and was developed with a quantitative approach, based on information obtained from historical data from the “Banco Central del Ecuador (ECB). The results obtained were presented by means of tests, such as, Hodrick-Prescott filter, Holt Winters test, Dickey-Fuller test for unit root, weapon regression with a lag and white noise test. It was determined, through the application of these tests, that the evolution of exports have been favorable for the economy in the last decade, except in 2012, where 2.32% decrease in exports is reflected due to strong winter, similarly, 2020 suffered an economic impact due to the pandemic, and according to the Winters Test, it will be analyzed that this decrease continues for 2021.
La exportación del banano es la primera actividad económica en la provincia de El Oro, la misma que ha generado gran impacto en los últimos años en el desarrollo económico del país, siendo una de las provincias con mayor porcentaje de exportación a nivel nacional, sin embargo, debido a las medidas oficiales de confinamiento obligatorio, por la pandemia mundial de COVID-19, las empresas se han visto obligadas a tomar medidas transitorias de reducción en la capacidad productiva. Por lo expuesto, actualmente la provincia de El Oro se encuentra gravemente afectada en sus exportaciones de banano. El presente estudio tiene como objetivo analizar la evolución en las exportaciones de banano y su impacto en el desarrollo económico de la provincia de El Oro 2011-2020, pre-pandemia y pandemia, mediante la aplicación de series de tiempo. Esta investigación es descriptiva, y se elaboró con un enfoque cuantitativo, basado en información obtenida de datos históricos del BCE, los resultados obtenidos fueron presentados mediante pruebas, tales como, Filtro de Hodrick- Prescott, Test de Holt Winters, Test de Dickey-Fuller para raíz unitaria, regresión Arma con un rezago y test de ruido blanco, con estas pruebas se determinó que la evolución de las exportaciones han sido favorables para la economía en la última década, a excepción del año 2012 en donde se refleja un decrecimiento de las exportación del 2,32% a causa del invierno, de forma similar, el año 2020 sufrió una afectación económica debido al pandemia, y según el Test Winters se prevé que este decrecimiento continúe para el 2021.
Keywords: PRODUCCIÓN; CRECIMIENTO ECONÓMICO; COMERCIO EXTERIOR; PROCESO DE COMERCIALIZACIÓN